In Memoriam: Timothy R. Parsons (1932–2022). (14th November 2022) - Perry, R. Ian
Abstract: One of the world's pre‐eminent marine scientists and the founding editor of Fisheries Oceanography, Professor Timothy (Tim) R. Parsons, passed away peacefully in hospital in April 2022. He was passionate about building a holistic understanding of how pelagic organisms are interconnected in the food‐webs of the sea, and about presenting alternative methods for the management of fisheries. For these activities and many others, he was the recipient of many international awards and honours. He had a profound influence on many students and colleagues, and leaves behind a foundational body of work on fisheries oceanography.